Encephalopathies Associated With Severe COVID-19 Present Neurovascular Unit Alterations Without Evidence for Strong Neuroinflammation. Issue 5 (September 2021) - Bernard-Valnet, Raphael; Perriot, Sylvain; Canales, Mathieu; Pizzarotti, Beatrice; Caranzano, Leonardo; Castro-Jiménez, Mayté; Epiney, Jean-Benoit; Vijiala, Sergiu; Salvioni-Chiabotti, Paolo; Anichini, Angelica; Salerno, Alexander; Jaton, Katia; et al.
Abstract : Objective: Coronavirus disease (COVID-19) has been associated with a large variety of neurologic disorders. However, the mechanisms underlying these neurologic complications remain elusive. In this study, we aimed at determining whether neurologic symptoms were caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) direct infection or by either systemic or local proinflammatory mediators. Methods: In this cross-sectional study, we checked for SARS-CoV-2 RNA by quantitative reverse transcription PCR, SARS-CoV-2–specific antibodies, and 49 cytokines/chemokines/growth factors (by Luminex) in the CSF +/− sera of a cohort of 22 COVID-19 patients with neurologic presentation and 55 neurologic control patients (inflammatory neurologic disorder [IND], noninflammatory neurologic disorder, and MS). Results: We detected anti–SARS-CoV-2 immunoglobulin G in patients with severe COVID-19 with signs of intrathecal synthesis for some of them. Of the 4 categories of tested patients, the CSF of IND exhibited the highest level of cytokines, chemokines, and growth factors. By contrast, patients with COVID-19 did not present overall upregulation of inflammatory mediators in the CSF. However, patients with severe COVID-19 (intensive care unit patients) exhibited higher concentrations of CCL2, CXCL8, and vascular endothelium growth factor A (VEGF-A) in the CSF than patients with a milder form of COVID-19. In addition, we could show that intrathecal CXCL8 synthesis was linked to an elevated albumin ratio and correlated with the increase of peripheral inflammation (serum hepatocyte growth factor [HGF] and CXCL10). Conclusions: Our results do not indicate active replication of SARS-CoV-2 in the CSF or signs of massive inflammation in the CSF compartment but highlight a specific impairment of the neurovascular unit linked to intrathecal production of CXCL8.